It’s not what it looks to be! : Déconnexion entre forme et sens dans les énoncés avec verbe de perception à emploi dit “copule” - Christelle LACASSAIN-LAGOIN (E-REA)
This paper aims at analysing the disconnection between form and meaning in sentences involving copular perception verbs (look, sound, smell, taste and feel). The origin of these verbs is a controversial issue, and in this article, it is argued that they have a nominal origin and that they have identical syntactic and semantic features. It appears that, in these copulative sentences, the grammatical subject does not coincide with the underlying subject of the verb, which has a modalising use as it expresses a judgment concerning sensory appearances. This surface conflict between syntax and semantics also shows in certain types of subject complements – nominal phrases, OF-prepositional phrases and AS IF/AS THOUGH-clauses. This study demonstrates that all subject complements necessarily refer to gradable properties, which is not the case with copular be. Thus, the copulative sentences in which perception verbs have a modalising use present many and various instances of semantic and syntactic reductions, motivated by the economy principle at work in discourse.